Analysis of technical-tactical factors in beach volleyball: a systematic review - Alvarado-Ruano, R.; Lopez-Martinez, A. B. (Cultura, Ciencia y Deporte, 2022)
The development of an effective performance is determined by a multidimensional character, being a combination of physical, technical, tactical, and psychosocial qualities. Sport technique is a fundamental aspect in the improvement process, influencing other aspects such as tactics. In beach volleyball, due to its sequential character, it is essential to study each of the technical actions. The aim of this study was to carry out a systematic review of the different articles published on the analysis of beach volleyball and to identify the criteria used for the analysis of technical-tactical components. The PRISMA guidelines were followed for this review. The databases PubMed, Web of Science and SportDiscus were searched. Based on the criteria, 33 articles were included. The results show a tendency towards the specific analysis of terminal actions versus continuity actions. The power serve was the most used in the men's category. In women's teams, the standing serve was the most used. The forearm reception was the most frequent. Women's teams tended to use forearm set more than men's teams. The spike was the most used in the men's category, while in the women's category it was the shot. The line block was the most used. Diagonal defense was the most used and effective.